2018
DOI: 10.1007/978-3-030-01784-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of External Debt: The Case of Malaysia

Abstract: I certify that this thesis satisfies the requirements as a thesis for the degree of Master of Science in Banking and Finance. Assoc. Prof. Dr. Nesrin Özataç Chair, Department of Banking and Finance We certify that we have read this thesis and that in our opinion it is fully adequate in scope and quality as a thesis for the degree of Master of Science in Banking and Finance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
1
11
1
Order By: Relevance
“…This paper used the autoregressive distributed lag (ARDL) structural break to empirically test the long and short run to determine Somalia's external debt from 1980 to 2018 and to examine the long-term with the error correction model to determine whether the variables have existing short-term relationships. This study employs and follows the existing framework determinants of foreign debt literature, such as Bittencourt (2015) and Gokmenoglu & Rafik (2018). Therefore, the basic specification of the model is presented as:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper used the autoregressive distributed lag (ARDL) structural break to empirically test the long and short run to determine Somalia's external debt from 1980 to 2018 and to examine the long-term with the error correction model to determine whether the variables have existing short-term relationships. This study employs and follows the existing framework determinants of foreign debt literature, such as Bittencourt (2015) and Gokmenoglu & Rafik (2018). Therefore, the basic specification of the model is presented as:…”
Section: Methodsmentioning
confidence: 99%
“…An interest ceiling is likely to be used as a debt liquidation tool that affects structural change, largely introduced after re-democratization, but is not expressed in the study carried out here as disparity does not affect the scale of the government. More recent studies found determinants of external debt, such as that of Gokmenoglu & Rafik (2018) who found that through increasing GDP the Malaysian government can afford to reduce external debt, which means that the government relies on GDP to repay foreign debt. Conversely, the amount of external controlling foreign debt.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Dawood et al (2021) suggest that economic growth decreases external debt, implying that as countries increase their income, they become less dependent on foreign debt and therefore reduce their borrowing. Likewise, Gokmenoglu and Rafik (2018) and Murwirapachena and Kapingura (2015) pointed out a negative relationship between economic growth and external debt. In the presence of the endogeneity issue, a simple OLS regression may yield spurious results (Bound et al, 1995;Staiger & Stock, 1997).…”
Section: Model Specificationsmentioning
confidence: 99%
“…In the context of our literature review, the majority of studies center on performing an influence analysis to evaluate the correlation between changes in specific variables and the level of debt (typically measured as either an absolute value or a percentage of GDP, although alternative methods exist-refer to the appendix). Other studies go a step further and engage in causality analyses, following, among others, the Granger approach (Mah et al 2013;Donayre and Taivan 2017;Gokmenoglu and Rafik 2018;Marire 2022). These analyses seek not only to identify associations between some variables such as government spending or economic growth (Donayre and Taivan 2017;De Vita, Trachanas and Luo 2018;Marire 2022) but also to determine whether variations in these variables actually cause changes in the level of debt or whether bidirectional relationships exist.…”
Section: Empirical Literaturementioning
confidence: 99%